Relevansi Maqāṣid Al-Syarī’ah dalam Strategi Manajemen Bisnis Syariah Kontemporer - Septian Fiktor Riyantoro; Sugiharti Sugiharti (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2026)
Studies on maqāṣid al-sharī‘ah in Islamic business have been widely conducted; however, most of them focus primarily on the normative aspects of Islamic law or its implementation within Islamic financial products and institutions. Research that specifically examines the relationship between maqāṣid al-sharī‘ah and the objectives and strategies of contemporary Islamic business management remains relatively limited, particularly in explaining how maqāṣid al-sharī‘ah can serve as a strategic framework that integrates economic objectives, ethical values, and business sustainability. This study aims to analyze the relevance of maqāṣid al-sharī‘ah to the objectives and strategies of contemporary Islamic business management. The study employs a library research method with a qualitative-descriptive approach by reviewing various academic sources, including scholarly journal articles, books, and relevant documents on maqāṣid al-sharī‘ah and Islamic business management. Data were analyzed using content analysis and conceptual synthesis to identify the interconnections between the dimensions of maqāṣid al-sharī‘ah and modern business management practices. The findings indicate that maqāṣid al-sharī‘ah possesses strong relevance as both a normative and strategic foundation for formulating organizational objectives, designing business strategies, strengthening corporate governance, developing human resources, and creating value for stakeholders. The integration of maqāṣid al-sharī‘ah into business management strategies contributes to enhancing the orientation toward maṣlaḥah (public welfare), fostering ethics-based competitive advantages, and ensuring long-term business sustainability. The novelty of this study lies in the development of a conceptual framework that positions maqāṣid al-sharī‘ah not merely as an instrument of sharia compliance, but also as a strategic paradigm for contemporary Islamic business management. This study enriches the literature on Islamic business management by offering an integrative perspective that bridges Islamic values with the practical demands of modern business management.